Estimativas para o estoque de carbono do solo ao longo de um gradiente topográfico na Amazônia Central - Freitas, Ana Carla Almeida de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
The growing concern with the increasing concentrations of greenhouse gases in the atmosphere and the resulting global warming has led the scientific community to question the role of soils as a source or sink of carbon. Due to the importance of estimates of carbon stocks in the soil and need for methods, reliable and capable of auditing, to estimate soil carbon stocks, this study aimed to understand how the system sampling influence on the estimates as sampling effort required for the determination of carbon stock and from this suggest equations for estimating the carbon stock in the soil depth. The study was conducted at the Experimental Station of Tropical Forestry of the National Institute for Amazon Research in Manaus region. Was collected from 90 sampling units distributed systematically in 40 hectares of primary forest, at 0-5, 5-10,10-20, 20- 30, 30-40, 40-50, 50-75 and 75 - 100 cm. Granulometry or texture analysis and soil density, quantification of carbon in the soil and subsequent calculation of carbon stock in the soil. The statistic used was ANOVA and post hoc Tukey analysis correlation and simple linear regression. The texture along the topographic gradient was very sandy loam plateau until the shoal. There was a decrease in carbon content with increasing depth and the opposite occurred that the soil density increased with depth. The plateau had the highest carbon content and low bulk density, while the shoal with the lowest carbon content and soil density. The plateau has a carbon stock of 98.14 ± 4.05 Mg C.ha-1, on the slope the stock was 92.64 ± 9.02 Mg C.ha-1, in the shallows stock was 65.52 ± 11.46 Mg C.ha-1 and considering the total area of the carbon stock was 92.75 ± 4.40 MgC.ha-1. It was observed that in areas of high topoghraphy variability, with different contours and soil types, systematic sampling was more efficient, with a lower sampling effort, contrasting with that observed in the stratified sampling suggests that a greater sampling effort, which can more difficult and expensive to collect. The equations for estimating the carbon stock in depth were adjusted for total area, without stratification and noted the need to collect in the lower layers when you want to know the stock at depth. The sampling plan for collecting soil in Central Amazonia, is suggested based on a systematic sampling, collecting in the 0-20 cm or 0- 40 cm, since these layers were highly correlated with the uncertainty and lower layers below and provided the best fit of equations to estimate the carbon stock in depth.
Keywords: Floresta Tropical – Mudanças Climáticas; Solos tropicais; Topossequência; Aquecimento global